Photoelectric sensors and controls selection and application - Juds, Scott M. (Mechanical engineering (Marcel Dekker, Inc.), 1988)
This excellent reference assembles into one source all pertinent information for matching sensors and controls with specific applications -- helping solve even the most difficult optical sensing and control problems. Requiring only minimal experience in enclosures, optics, electronics, and industrial controls, Photoelectric Sensors and Controls explains fundamental concepts in easy-to-understand terms, backed with helpful diagrams ... gives in-depth analysis of major sensor configurations ... describes electrical control interfaces, control logic functions, and specifications ... provides definitions of technical terms in clear and concise language ... discusses the value of product test standards ... covers the effect of environmental issues on system reliability ... and contains more than 70 application examples that clarify the possibilities, limitations, and pitfalls of photoelectric sensors and controls. Richly illustrated with over 300 drawings, photographs, graphs, and tables, this resource is invaluable reading for engineers, designers, and manufacturers involved with sensor applications; professional seminars; and technical school and undergraduate courses in optical sensing and control.